Hospital wastewaters treatment: Fenton reaction vs. BDDE vs. ferrate(VI) - Mackuľak, Tomáš; Grabic, Roman; Špalková, Viera; Belišová, Noemi; Škulcová, Andrea; Slavík, Ondřej; Horký, Pavel; Gál, Miroslav; Filip, Jan; Híveš, Ján; Vojs, Marian; Staňová, Andrea Vojs; et al. (Environmental science and pollution research international, 2019)
Various types of micropollutants, e.g., pharmaceuticals and their metabolites and resistant strains of pathogenic microorganisms, are usually found in hospital wastewaters. The aim of this paper was to study the presence of 74 frequently used pharmaceuticals, legal and illegal drugs, and antibiotic-resistant bacteria in 5 hospital wastewaters in Slovakia and Czechia and to compare the efficiency of several advanced oxidations processes (AOPs) for sanitation and treatment of such highly polluted wastewaters. The occurrence of micropollutants and antibiotic-resistant bacteria was investigated by in-line SPE-LC-MS/MS technique and cultivation on antibiotic and antibiotic-free selective diagnostic media, respectively. The highest maximum concentrations were found for cotinine (6700 ng/L), bisoprolol (5200 ng/L), metoprolol (2600 ng/L), tramadol (2400 ng/L), sulfamethoxazole (1500 ng/L), and ranitidine (1400 ng/L). In the second part of the study, different advanced oxidation processes, modified Fenton reaction, ferrate(VI), and oxidation by boron-doped diamond electrode were tested in order to eliminate the abovementioned pollutants. Obtained results indicate that the modified Fenton reaction and application of boron-doped diamond electrode were able to eliminate almost the whole spectrum of selected micropollutants with efficiency higher than 90%. All studied methods achieved complete removal of the antibiotic-resistant bacteria present in hospital wastewaters.
Keywords: Hospitals; Hydrogen Peroxide; Medical Waste; odpad tekutý - odstraňování; Fenton-like reaction; diamant; Illicit Drugs; zakázané drogy; chemické látky znečišťující vodu; nemocnice; Wastewater; železo; Ferrate(VI); Water Pollutants, Chemical; Tandem Mass Spectrometry; Boron; Hospital effluents characterization; Slovakia; peroxid vodíku; Chromatography, Liquid; Waste Disposal, Fluid; Pharmaceutical Preparations; Diamond; bakteriální léková rezistence; odpadní voda; léčivé přípravky; oxidace-redukce; Boron-doped diamond electrode; Electrodes; tandemová hmotnostní spektrometrie; Oxidation-Reduction; Czech Republic; Iron; Waste Water; Česká republika; elektrody; Slovenská republika; bor; zdravotnický odpad; Drug Resistance, Bacterial; Antibiotic-resistant bacteria; chromatografie kapalinová